COMPUTING EXPERIMENTS FOR CALCULATION OF ELECTROSTATIC AXISYMMETRIC FIELD IN PIECEWISE-HOMOGENEOUS INSULATION WITH SPHERICAL INCLUSIONS - A.V. Bezprozvannych (National Technical University "Kharkiv Polytechnic Institute", 2014)
Calculations of electrostatic axisymmetric field are made with application of solution to Fredholm integral equation of the first and the second kinds in a piecewise homogeneous isotropic linear polymeric insulation. On the basis of numerical experiments via a Matlab-based program, influence of the number of nodes on the numerical solution accuracy is analysed and the order of the resolving system of linear algebraic equations within small distances between spherical inclusions is validated.